2020
DOI: 10.3390/brainsci10090649
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Assisted Behavioral Intervention for Families with Children with Autism Spectrum Disorders: A Randomized Control Trial

Abstract: Background: Telehealth is useful for both autism spectrum disorder (ASD) diagnosis and treatment, but studies with a direct comparison between teletherapy and traditional in-person therapy are limited. Methods: This randomized control trial—ISRCTN (International Standard Randomised Controlled Trial Number) primary clinical trial registry ID ISRCTN15312724—was aimed at comparing the effect of a tele-assisted and in-person intervention based on a behavioral intervention protocol for families with children affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…Applied Behavior Analysis (ABA) Four studies examined the possibility of using ABA across telehealth platforms (Fisher et al, 2020;Marino et al, 2020;Subramaniam et al, 2017;Yi & Dixon, 2021) One study utilized VC to aid parents via telehealth to deliver discrete-trial instruction (DTI), an intervention based upon applied behavior analysis (ABA), with their children with ASD (Subramaniam et al, 2017). Parents first received necessary in-person behavioral skills training on how to implement the DTI procedures and then trainers conducted VC sessions with the parents and provided immediate feedback after each session; parents continued to have high treatment integrity with remote supervision months following the initial training (Subramaniam et al, 2017).…”
Section: Social Communication Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Applied Behavior Analysis (ABA) Four studies examined the possibility of using ABA across telehealth platforms (Fisher et al, 2020;Marino et al, 2020;Subramaniam et al, 2017;Yi & Dixon, 2021) One study utilized VC to aid parents via telehealth to deliver discrete-trial instruction (DTI), an intervention based upon applied behavior analysis (ABA), with their children with ASD (Subramaniam et al, 2017). Parents first received necessary in-person behavioral skills training on how to implement the DTI procedures and then trainers conducted VC sessions with the parents and provided immediate feedback after each session; parents continued to have high treatment integrity with remote supervision months following the initial training (Subramaniam et al, 2017).…”
Section: Social Communication Interventionsmentioning
confidence: 99%
“…During Phase 2 all parents received 2-h weekly group behavioral therapy and all children received 1 h per week of individualized ABA therapy for 12 weeks. Lastly, during Phase 3, for 12 weeks, parents in the telehealth group received 2-h per week one-on-one behavioral training and coaching while the control group received 2-h per week in-person treatment (Marino et al, 2020) Results demonstrated a decrease in parent-reported stress related to child's challenging behaviors and improvements in their perception on how to manage these behaviors was seen in the telehealth group only (Marino et al, 2020). Another study examined the efficacy of parent implementation of early intensive behavioral intervention skills via telehealth using parent-child dyads, where one parent received the intervention and other parent was in the control group (Fisher et al, 2020).…”
Section: Social Communication Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three group design studies (i.e., DuPaul et al, 2018;Lindgren et al, 2020;Marino et al, 2020) also evaluated interventions to reduce problem behavior and met all indicators. As there were not enough group design studies to warrant aggregation, we instead present the details of the individual studies to discuss the evidence they provide towards establishment of behavioral reduction interventions via telehealth as an evidence-based practice.…”
Section: Behavior Reductionmentioning
confidence: 99%
“…The second group design study by Marino et al (2020) evaluated the coaching of parents in "ABA protocol" and the intervention effects on problem behavior as measured using the Home Situation Questionnaire modified for children with ASD (HSQ-ASD). The authors did not provide specification regarding ABA procedures taught to the parents (e.g., intervention) but identified substantial improvements regarding parent ratings of the participating child's behavior.…”
Section: Behavior Reductionmentioning
confidence: 99%